The love of painting : genealogy of a success medium - Graw, Isabelle; Dunphy, Niamh (Berlin : Sternberg Press, 2018)
Painting seems to have lost its dominant position in the field of the arts. However, looking more closely at exhibited photographs, assemblages, installations, or performances, it is evident how the rhetorics of painting still remain omnipresent. Following the tradition of classical theories of painting based on exchanges with artists, Isabelle Graw's The Love of Painting considers the art form not as something fixed, but as a visual and discursive material formation with the potential to fascinate owing to its ability to produce the fantasy of liveliness. Thus, painting is not restricted to the limits of its own frame, but possesses a specific potential that is located in its material and physical signs. Its value is grounded in its capacity to both reveal and mystify its conditions of production. Alongside in-depth analyses of the work of artists like Édouard Manet, Jutta Koether, Martin Kippenberger, Jana Euler, and Marcel Broodthaers, the book includes conversations with artists in which Graw's insights are further discussed and put to the test.
The economy of painting : reflections on the particular value form of the painted canvas -- Questions of value : a conversation between Kerstin Stakemeier and Isabelle Graw -- Acknowledgments -- Author biography -- Bibliographic note -- Image credits.
boek
Keywords: Painting -- History